Utility of MLH1 Methylation Analysis in the Clinical Evaluation of Lynch Syndrome in Women with Endometrial Cancer - Amanda Bruegl; Bojana Djordjevic; Diana L. Urbauer; Shannon N. Westin; Pamela T. Soliman; Karen Lu; Rajyalakshmi Luthra; Russell R. Broaddus (2014)
Clinical screening criteria, such as young age of endometrial cancer diagnosis and family history of signature cancers, have traditionally been used to identify women with Lynch Syndrome, which is caused by mutation of a DNA mismatch repair gene. Immunohistochemistry and microsatellite instability analysis have evolved as important screening tools to evaluate endometrial cancer patients for Lynch Syndrome. A complicating factor is that 15-20% of sporadic endometrial cancers have immunohistochemical loss of the DNA mismatch repair protein MLH1 and high levels of microsatellite instability due to methylation of MLH1. The PCR-based MLH1 methylation assay potentially resolves this issue, yet many clinical laboratories do not perform this assay. The objective of this study was to determine if clinical and pathologic features help to distinguish sporadic endometrial carcinomas with MLH1 loss secondary to MLH1 methylation from Lynch Syndrome-associated endometrial carcinomas with MLH1 loss and absence of MLH1 methylation. Of 337 endometrial carcinomas examined, 54 had immunohistochemical loss of MLH1. 40/54 had MLH1 methylation and were designated as sporadic, while 14/54 lacked MLH1 methylation and were designated as Lynch Syndrome. Diabetes and deep myometrial invasion were associated with Lynch Syndrome; no other clinical or pathological variable distinguished the 2 groups. Combining Society of Gynecologic Oncology screening criteria with these 2 features accurately captured all Lynch Syndrome cases, but with low specificity. In summary, no single clinical/pathologic feature or screening criteria tool accurately identified all Lynch Syndrome-associated endometrial carcinomas, highlighting the importance of the MLH1 methylation assay in the clinical evaluation of these patients.